2008
DOI: 10.1007/s11104-008-9824-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and daily time course of the 13C composition in soil CO2 efflux recorded with a tunable diode laser spectrophotometer (TDLS)

Abstract: Temporal variations of carbon isotope composition of soil CO 2 efflux (F S and δ 13 C FS ) at different time scales should reflect both temporal variations of the climate conditions that affect canopy functioning and temporal changes in the relative contribution of autotrophic respiration to total F S . A tunable diode laser spectrophotometer (TDLS) was installed in the Hesse forest (northeast of France) early during the 2007 growing season to determine the seasonal and daily variability in δ 13 C FS . This me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
3
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 38 publications
5
52
3
2
Order By: Relevance
“…The results reported here are consistent with many previous studies, in which a heavier isotopic source value is observed during drier and warmer seasons compared to the colder and wetter months of the year (Ekberg et al, 2007;Marron et al, 2009;Goffin et al, 2014). Other studies have related the variations in the δ 13 C of ecosystem and soil respiration to air humidity (Ekblad and Högberg, 2001;Bowling et al, 2002;Ekblad et al, 2005).…”
Section: Sources Of Variation In δ 13supporting
confidence: 92%
“…The results reported here are consistent with many previous studies, in which a heavier isotopic source value is observed during drier and warmer seasons compared to the colder and wetter months of the year (Ekberg et al, 2007;Marron et al, 2009;Goffin et al, 2014). Other studies have related the variations in the δ 13 C of ecosystem and soil respiration to air humidity (Ekblad and Högberg, 2001;Bowling et al, 2002;Ekblad et al, 2005).…”
Section: Sources Of Variation In δ 13supporting
confidence: 92%
“…3, 5 and S1). Several studies have reported diel variation in the δ 13 C of the soil efflux (Bahn et al, 2009;Kodama et al, 2008;Marron et al, 2009), but in our case there was no diel variation in the δ 13 C of soil respiration (neither δ R , Fig. 5 nor δ J , Fig.…”
Section: Discussioncontrasting
confidence: 68%
“…Trying to accurately measure a 3% difference between two air streams (the chamber inflow and outflow) can be challenging, especially in the field. Using this type of open chamber to measure the d 13 CR S at natural abundance levels is clearly possible, as demonstrated recently, [11,68] but at low surface efflux rates there is a diminishing difference between the in-flowing and out-flowing chamber air (Fig. 3).…”
Section: Open Chambersmentioning
confidence: 56%
“…Because the TDLS and CRDS systems are less bulky and have lower power requirements than the IRMS instruments, they are more portable than the IRMS systems and they can be used in the field ( measurements. [11,13,56] The precision of the isotope measurements achievable with these systems is generally lower than that of IRMS (although the gap is closing), sample introduction systems for gases tend to be bespoke designs, and instrument control software is still an active area of development. However, the ability of these instruments to provide real-time isotope analysis in the field has opened up new and exciting possibilities across a variety of disciplines; this includes the characterisation of d 13 CR S .…”
Section: Analysis By Mass Spectrometry or Laser Absorptionmentioning
confidence: 99%
See 1 more Smart Citation